Mobility of lysozyme in poly(L-lysine)/hyaluronic acid multilayer films - Velk, Natalia; Uhlig, Katja; Vikulina, Anna S.; Duschl, Claus; Volodkin, Dmitry (Colloids and Surfaces B: Biointerfaces, 2016)
The spatial and temporal control over presentation of protein-based biomolecules such as growth factors and hormones is crucial for in vitro applications to mimic the complex in vivo environment. We investigated the interaction of a model protein lysozyme (Lys) with poly(L-lysine)/hyaluronic acid (PLL/HA) multilayer films. We focused on Lys diffusion as well as adsorption and retention within the film as a function of the film deposition conditions and post-treatment. Additionally, an effect of Lys concentration on its mobility was probed. A combination of confocal fluorescence microscopy, fluorescence recovery after photobleaching, and microfluidics was employed for this investigation. Our main finding is that adsorption of PLL and HA after protein loading induces acceleration and reduction of Lys mobility, respectively. These results suggest that a charge balance in the film to a high extent governs the protein–film interaction. We believe that control over protein mobility is a key to reach the full potential of the PLL/HA films as reservoirs for biomolecules depending on the application demand.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Diffusion; FRAP; Layer-by-layer; Protein; Release